STUDY ON NONLINEAR DYNAMIC CHARACTERISTICS OF DRIVING SYSTEM OF SHEARER CUTTING MACHINE WITH CLEARANCE - XIE Mao; LIU XiFu; Fu ChunTian; YU HaiYang (Jixie qiangdu)
In order to study the nonlinear dynamic characteristics of the cutting system of the shearer with gap,a dynamic model of the gear system of the shearer cutting machine is established,and the function of meshing stiffness and damping in the model is established. The influence of the tooth clearance on the meshing force of the gears of the shearer’s drive system is studied by using the runge-Kuatt method. The results show that the gears are increased by the gears The change of the meshing force and the amplitude of the frequency multiplication of the meshing frequency. Increasing the amplitude of the tooth side increases the fluctuation range of the engaging force,causing a large impact force in the transmission process,accelerating the wear of the tooth surface,The gears are broken in gear due to overload. Improve the stability and service life of the gear train of the shearer cutting section,and reduce the torsional vibration degree and reduce the tooth clearance. This study provides a theoretical basis for the optimal design and research of gear transmission system.